Stereotactic Ablative Radiotherapy with CyberKnife in the Treatment of Locally Advanced Prostate Cancer: Preliminary Results. Issue 6 (November 2015) - Fan, Chao-Yueh; Chao, Hsing-Lung; Huang, Wen-Yen; Lin, Chun-Shu; Chen, Chang-Ming; Lo, Cheng-Hsiang
Aims and Background: Recent clinical reports of stereotactic ablative radiotherapy (SABR) in the treatment of low-risk prostate cancer have been encouraging. Our study evaluates the efficacy and safety of SABR using the CyberKnife system for treating intermediate- to very-high-risk prostate cancer. Methods and Study Design: Between May 2010 and June 2013, 31 patients (15 intermediate risk, 14 high risk, and 2 very high risk) without pelvic lymph node metastasis were enrolled retrospectively. The treatment consisted of 37.5 Gy in 5 fractions over 1-2 weeks using CyberKnife SABR. Twenty-five patients (81%) received androgen deprivation therapy (ADT). Biochemical failure was defined using the nadir + 2 criterion. Toxicity was assessed with the Common Terminology Criteria of Adverse Events (version 4). Results: The median follow-up was 36 months (range 7-58 months). The median pretreatment prostate-pecific antigen (PSA) was 13.5 ng/mL (range 4.5-124.0 ng/mL). The median PSA decreased to 0.09 ng/mL (range <0.04-5.38 ng/mL) and 0.12 ng/mL (range <0.04-2.63 ng/mL) at 6 months and 12 months after SABR, respectively. The 3-year biochemical relapse-free survival was 90.2% for all patients, 100% for the intermediate-risk patients, and 82% for the high- and very-high-risk patients (p = 0.186). No patient experienced ≥ grade 3 toxicity. There were 7 acute and 5 late grade 2 genitourinary toxicities and 1 acute and no late grade 2 gastrointestinal toxicity. Conclusions: Our preliminary results support that CyberKnife SABR with ADT is safe and feasible in patients with intermediate- to high-risk prostate cancer. A further large-scale clinical trial with longer follow-up is warranted.